Artificial Intelligence Vs My Future Job: Perceptions of Asian Undergraduates - Anthony Nnamdi Ogbolu; Sukidjo Sukidjo (Journal of Robotics and Control (JRC), 2020)
Artificial Intelligence (AI) could have far reaching impact on economies and societies across the globe. The current avalanche of technological changes across the workplace demonstrated by AI has rekindled widespread fear of job losses and increase in inequality. This study sets out to analyze the perceptions of Asian undergraduates towards the increasing development of AI technologies in the workplace and assess how confident and adaptable they are in relation to challenges of AI as a viable future job competitor in the labour market. A survey instrument was administered randomly to 84 respondents from Yogyakarta State University and descriptive statistics was used in analyzing the data. The findings from the study revealed that more than 70 percent of respondents possess satisfactory levels of self-confidence and adaptability skills to take on the disruptive forces of AI technologies in the future but exhibits mixed feeling as regard to their perception of AI technologies in the workplace as the margin of difference among the three response options provided (Scared, Confident or Indifferent) were so small and below 50% for each option.  This study bridges the gap in the literature relating to undergraduate’s perception of AI in the workplace especially in Asia while also providing useful insights and recommendations to ensuring that all relevant stakeholders especially undergraduates maximizes the opportunities brought about by AI while reducing or totally eradicating the threats on their path.